A Controlled Pilot Study of the Wish Outcome Obstacle Plan Strategy for Spouses of Persons With Early-Stage Dementia. (25th June 2021) - Monin, Joan K; Oettingen, Gabriele; Laws, Holly; David, Daniel; DeMatteo, Lyndsay; Marottoli, Richard
Abstract: Objectives: Behavioral interventions can reduce distress for couples coping with early-stage dementia. However, most interventions are limited in accessibility and fail to address individualized goals. This pilot study examined the dyadic effects on multiple indicators of well-being of the Wish Outcome Obstacle Plan (WOOP) intervention, which guides participants to use Mental Contrasting with Implementation Intentions to achieve attainable goals in their daily lives. Methods: This randomized controlled trial included 45 older persons with early-stage dementia (PWD) and their spousal care partners (CPs: n = 90 individuals). CPs were assigned randomly to WOOP training immediately after baseline (WOOP) or after a 3-month follow-up interview (Control; CON). Both groups received a dementia care education booklet. WOOP CPs were instructed to practice WOOP at least once a day for 2 weeks. All CPs and PWDs completed home surveys (baseline, 2 weeks, and 3 months), measuring perceived stress, depressive symptoms, quality of life, and affect. Results: Mixed-effects models showed significant intervention × time interaction effects with large effect sizes for CPs on three of the five outcomes over 3 months. Compared with CON, WOOP CPs had decreased perceived stress (δ = 1.71) and increased quality of life (δ = 1.55) and positive affect (δ = 2.30). WOOP PWD showed decreased perceived stress (δ = 0.87) and increased quality of life (δ = 1.26), but these effects were not statistically significant. Discussion: WOOP is a promising, brief intervention to improve dementia CPs' well-being that may also positively affect their partners with dementia.